Sonho de uma noite de verão: recriações, autonomias e abismos - Asevedo, Marcial de (2012)
This research project in performing arts has as main objectives to build a creative process on the piece s A Midsummer Night Dream by Wiliam Shalespeare, and analysis of records and documentation to theories and concepts that lie in this Theatre contemporaneity. It stimulates the creation of experimentation scenic body of the characters and conflicts, with different methodologies and theatrical languages, which werw organized as a scenic choreography, realistic scenes, commedia dell arte, Butoh and performance-art. Concepts such as movement, action, narrative, physical condition, fiction and reality are addressed in practice and as a sign of experiments scene. The method od analysis is guided in account of the experiences, supported by theories of languages mentioned above, records created by actors anda scenic exercise recording on DVD. The completion of work fits in matters academic training for actor, such as stage presence, and vocal and body instrumentaliztation, subjectivity and interpretation, and still urgent need for ongoing dialogue between personal expression and collective communication. The process converged apparently opposing methodologies and languages, order a polyphony of routes and directions. Trying to approach multifaceted language of dreams, full of symbolism and implicit ways os meaning and content.